Laparoscopic cholecystectomy: the first 155 patients. - Rees, B. I. (Royal College of Surgeons of England, 1992)
Laparoscopic cholecystectomy has been attempted in 155 patients. Eight patients required conversion to open cholecystectomy (5%): three owing to lack of clear anatomical detail, two procedures were abandoned because of instrument failure, two had a dilated common bile duct on cholangiography, and one owing to a very adherent mucocele of the gallbladder. Cholangiography was performed selectively; successfully completed in 45 (22% of all patients). Common bile duct stones were found in two patients. All patients were drained, with two bile leaks, one requiring a laparotomy. There was one ductal injury. Most patients (85%) were discharged within 48 h. This initial experience suggests laparoscopic cholecystectomy is the procedure of choice for most patients with symptomatic cholelithiasis.